Evaluating the readability of marketing research textbooks: an international comparison. (29th April 2014) - Berndt, Adele; P. Wayland, Jane
Abstract : Purpose: – Locally authored textbooks are used at tertiary South African institutions to assist in marketing research studies. The purpose of this paper is to investigate the readability of locally authored marketing research textbooks in South Africa and compare them with international (USA) texts. Design/methodology/approach: – South African marketing research textbooks (authored locally) used at South African institutions were identified. Electronic versions of the textbooks were used and analysed using accepted readability formulae. The same procedure was used with texts produced in the USA and the findings of each were compared. Findings: – The South Africa texts scored higher on the Flesch Reading Ease score than US texts, which links to the target audience of these books (undergraduate students), while also being cognisant of the reading skills of the target audience but their score still describes them as "difficult". Research limitations/implications: – The original formulae and theory tend to be dated, though there are recent studies into readability in other areas of business studies. There are also those that question the applicability of readability formulae in the tertiary environment. Practical implications: – Instructors need to ensure that material is at a suitable reading level to maximise the student's learning. For publishers and authors, this means that the examples and illustrations used need to be linked to the context in which the student lives and functions, and not just focus on the English used in the text. Originality/value: – While studies have been conducted into the readability of US textbooks, there is little published research into the readability of regional marketing research textbooks in other contexts to facilitate comparison.